The Power of Yoga - Miss. Sumitra Das, Miss. Marina Rai, Dr. P. Yoga, Dr. K. Alaguraja, Dr. K. Selvakumar (International Journal of Advanced Science and Technology, 2020)
The word Yoga, itself sounds very soulful and divine. Today, yoga is very trending among the people from old age to youngsters who want to run their life smoothly as it covers a broad range of benefits in human’s life. Yoga is a method, art or discipline that have been practicing since ancient times to promotes good physical and mental health through postures and breathing technique and synchronizing the body and mind together to achieve the harmony in life. Every move makes in yoga is done very smoothly and calmly. Yoga enhances the muscles, tendons, and ligaments move through a full range of motion decreasing the chances of getting injured and making bones healthy. Yoga is for everyone and every sport. Yoga toils on strength, flexibility, balance, coordination, agility, endurance, core strength and overall strength. Athletes today include yoga on their training schedule as it works on the overall body.